The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4103/0972-2327.44558
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Epalrestat, an aldose reductase inhibitor, in diabetic neuropathy: An Indian perspective

Abstract: Background:A number of diabetic patients with diabetic neuropathy, in India, were treated with epalrestat, an aldose reductase inhibitor. In this study, more than 2000 patients with diabetic neuropathy, who were treated with epalrestat for 3-12 months, were analyzed to assess the efficacy and the adverse reactions of the drug.Method:We analyzed the subjective symptoms (spontaneous pain, numbness, coldness and hypoesthesia) and the nerve function tests (motor nerve conduction velocity, sensory nerve conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Epalrestat, a classical AR inhibitor, inhibited the activity and protein expression of AR in hypertensive cardiac and vascular diseases (Wang et al, 2007;Ramirez and Borja, 2008;Sharma and Sharma, 2008;Gu et al, 2010). The effects of Epalrestat on the expression of AR mRNA and protein in hypertensive renal injury were confirmed by us both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…Epalrestat, a classical AR inhibitor, inhibited the activity and protein expression of AR in hypertensive cardiac and vascular diseases (Wang et al, 2007;Ramirez and Borja, 2008;Sharma and Sharma, 2008;Gu et al, 2010). The effects of Epalrestat on the expression of AR mRNA and protein in hypertensive renal injury were confirmed by us both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…Epalrestat reduces aldose reductase inhibitor, helps to reduce the sorbitol levels used in diabetic neuropathy [29]. It was found to be most effective in subjects with good glycaemic control and well tolerated [30]. Hypoglycaemia with glybenclamide and weight gain, oedema, precipitation of CCF, hepatotoxicity with Pioglitazone are the common adverse effects encountered.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial in India, more than 2000 patients with diabetic neuropathy were treated with epalrestat for 3-12 months, the results showed that the improvement rate of the subjective symptoms was 75% and that of the nerve function tests 36%. Adverse drug reactions were encountered in 52 (2.5%) of the 2190 patients, none of which was severe [90]. Although data are limited, it is strongly suggested that epalrestat is a highly effective and safe agent for the treatment of diabetic neuropathy.…”
Section: Epalrestatmentioning
confidence: 99%